Bordetella bronchiseptica Pneumonia in an Extremely-Low-Birth-Weight Neonate - Ting, Yuk Joseph; Ho, Pak-leung; Wong, Kar-yin (American Journal of Perinatology Reports, 2011)
Bordetella bronchiseptica, a gram-negative coccobacillus, is a common veterinary pathogen. In both domestic and wild animals, this bacterium causes respiratory infections including infectious tracheobronchitis in dogs and atrophic rhinitis in swine. Human infections are rare and have been documented in immunocompromised hosts. Here, we describe an extremely-low-birth-weight infant with B. bronchiseptica pneumonia. This is the first report that describes the microorganism's responsibility in causing nosocomial infection in a preterm neonate. He recovered uneventfully after a course of meropenem. It is possible that the bacteria colonize the respiratory tracts of our health care workers or parents who may have had contact with pets and then transmitted the bacterium to our patient. Follow-up until 21 months of age showed normal growth and development. He did not suffer from any significant residual respiratory disease.
Keywords: Bordetella bronchiseptica; extremely low birth weight; preterm; neonate